Perception, terminology and speakers of legal discourse in the text specialisation degree - Rodríguez Tapia, Sergio (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This paper analyses the text specialisation degree of legal discourse. To this end, based on the discursive foundations of the Communicative Theory of Terminology and the Socio-Cognitive Theory of Perception, and using corpus linguistics, a database containing information on six variables, both linguistic and extralinguistic (the type of text, lexical variety, reformulation, terminological density, the role of the interlocutors and the type of text), has been analysed using a correlational method with a quantitative-qualitative approach, which has been complemented with automatic learning. The results show the complexity of legal discourse, given the difficulty of finding clear patterns of behavior in various variables, especially when compared with other disciplines such as medicine.